Reconstruction of the asbestos exposure in a textile company producing sewing threads through the use of an unusual information source - Angelini, Alessia; Chellini, Elisabetta; Parducci, Dino; Puccetti, Monica; Mauro , Luigi (La Medicina del Lavoro, 2020)
Background: The Tuscan Regional Operating Center (ROC) of Malignant Mesotheliomas has identified a cluster of 11 cases of malignant mesothelioma occurred in a textile plant manufacturing sewing thread. Using the common research method, the ROC had not previously been able to identify the specific sources of asbestos exposure causing such a large cluster. Objectives: The ROC’s objective was to review all cases of the cluster and to better identify their occupational asbestos exposures. Methods: The cases’ occupational histories of asbestos exposure have been reviewed, using information deriving from the annual reports sent to the Tuscany Region since 1988 by all the asbestos removal companies according to the Law no. 257/1992, article 9, and from interviews to former employees of the plant. Results: The work cycle has been reconstructed and enriched with the new information about the asbestos presence and its uses in the plant. The eleven cases were all reclassified as “certainly occupational exposed” given that the new collected information depicted a widespread asbestos pollution of the workplace during the period of employment of all cases. Conclusions: Using different sources of information, in addition to those traditionally collected through questionnaires, to reconstruct past asbestos exposuresallowed us to clarify the existence of the cluster of mesothelioma cases and the highest level of occupational asbestos exposure was attributed to all cases with consequent activation of the medico-legal procedure.